Pemanfaatan Air Hujan Untuk Memenuhi Kebutuhan Air Baku Jangka Panjang Ibu Kota Negara - Teddy W Sudinda (Universitas Trisakti, 2020)
The supply of raw water to meet the availability of drinking water for the new State Capital (IKN) needs to be guaranteed in a sustainable manner. This research was conducted to analyze the potential for raw water in the vicinity of the new capital city. One of the problems faced by the new IKN is the problem of raw water availability to meet drinking water needs. The new IKN will result in the movement of large numbers of people, so that it will require a large supply of raw water for the supply of drinking water. The government wants the quantity of raw water to meet the needs of the IKN. At present, the condition in the IKN area is that the availability of raw water for drinking water is still very limited in quantity. Therefore, it is necessary to conduct research to find alternative sources of raw water by examining the Potential Utilization of Rainwater (PAH) in the IKN Region to meet the projected raw water needs for the years 2023-2073.